2018
DOI: 10.1021/acs.jpca.7b11235
|View full text |Cite
|
Sign up to set email alerts
|

Role of Methyl-2-nitrophenol Photolysis as a Potential Source of OH Radicals in the Polluted Atmosphere: Implications from Laboratory Investigation

Abstract: Methyl-substituted 2-nitrophenols are important components of "brown carbon" from biomass burning. Photolysis is their major gas-phase degradation pathway. To determine the extent of light absorptions by 4-methyl-2-nitrophenol and 5-methyl-2-nitrophenol, we obtained their absorption cross sections in the 295-400 nm region by using cavity ring-down spectroscopy. Cross-section values for 4-methyl-2-nitrophenol were (1.01 ± 0.07) × 10, (5.72 ± 0.39) × 10, and (1.80 ± 0.17) × 10 cm/molecule at 295, 345, and 400 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
(107 reference statements)
1
23
0
Order By: Relevance
“…This was more likely associated with the fact that particle-phase NPs only account for a minor part of the atmospheric NP abundance due to the high vapor pressure of NPs (Table S1). The abundance of particulate NP could largely depend on gas-to-particle partitioning, which is strongly affected by temperature, as well as their gas-phase loss pathways (e.g., photolysis) (Bejan et al, 2007;Yuan et al, 2016;Sangwan and Zhu, 2018). NC and MNC were mainly present in the particle phase (Table S1).…”
Section: Temporal Variations and Sources Of Nacsmentioning
confidence: 99%
“…This was more likely associated with the fact that particle-phase NPs only account for a minor part of the atmospheric NP abundance due to the high vapor pressure of NPs (Table S1). The abundance of particulate NP could largely depend on gas-to-particle partitioning, which is strongly affected by temperature, as well as their gas-phase loss pathways (e.g., photolysis) (Bejan et al, 2007;Yuan et al, 2016;Sangwan and Zhu, 2018). NC and MNC were mainly present in the particle phase (Table S1).…”
Section: Temporal Variations and Sources Of Nacsmentioning
confidence: 99%
“…Yuan et al (2016) have reported that photolysis was the most efficient loss pathway for nitrophenol in the gas phase. Different values of absorption cross sections and quantum yields for nitrophenol have been reported (Chen et al, 2011;Sangwan and Zhu, 2018;Bejan et al, 2006). In this study, we used the values from Chen et al (Chen et al, 2011), which can reproduce well the observed concentrations of nitrophenol and methyl nitrophenol during the measurement period.…”
Section: E2mentioning
confidence: 97%
“…Visibility and planetary boundary layer (PBL) height were measured using a visibility sensor (PWD22, Vaisala) and a ceilometer (CL51,Vaisala), respectively 2.2 HONO budget calculation. Multiple sources of ambient HONO have been identified, such as emission from soil (Esoil) (Oswald et al, 2015;Meusel et al, 2018) and vehicle exhaust (Evehicle) (Trinh et al, 2017), production through homogeneous reaction between NO and OH (PNO-OH) in the atmosphere, photolysis of nitrate (Pnitrate) (Bao et al, 2018), nitrous acid (PHNO3) and nitrophenenol (Pnitrophenol) (Sangwan and Zhu, 2018), heterogeneous reaction of NO2 on aerosol surface (Paerosol) and ground surface (Pground) (Liu et al, 2019c;Li et al, 2018;Wang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%